Activated circulating T follicular helper 17 cells positively correlated with anti-HBV humoral immunity in chronic hepatitis B patients - Gu, Qi; Mao, Minxin; Liu, Yuan; Tong, Xin; Zhang, Juan; Ran, Jinqiu; Ma, Xiaoyan; Xia, Juan; Huang, Rui; Li, Jie; Liu, Tianyang; Chen, Yuxin; et al. (Frontiers in Microbiology, 2026)
IntroductionDysfunction of hepatitis B virus (HBV)-specific B cells and lack of antibodies against hepatitis B surface antigen (HBsAg) are associated with failure to achieve functional cure in chronic hepatitis B (CHB). Follicular helper T (Tfh) cells are essential for B-cell differentiation into plasma cells and comprise three subsets: Tfh1, Tfh2, and Tfh17 cells. Our previous studies suggested dysregulated Tfh responses in CHB patients. However, the functions of Tfh cell subsets in CHB progression and treatment remain incompletely characterized.MethodsTo explore the role of Tfh subgroups in HBV infection, we analyzed the frequencies of total and HBsAg-specific Tfh cell subsets and their surface markers using flow cytometry.ResultsCompared with healthy individuals [healthy controls (HCs)], CHB patients had significantly higher frequencies of total Tfh cells, lower frequencies of Tfh17 cells and increased PD-1 expression. The frequency of quiescent Tfh17 cells negatively correlated with HBsAg+ B cells and positively correlated with total immunoglobulin G (IgG). Further analysis revealed positive correlations between the frequency of quiescent Tfh17 cells and IgG1 and IgG3 levels.DiscussionThese results suggest that Tfh17 frequency varies across immune phases in chronic HBV infection and that Tfh17 cells correlate with the immune response against chronic HBV infection.ImportanceHBV is a major global public health problem. Dysfunction of HBV-specific B cells is an important reason for the failure to achieve a functional cure for HBV. Tfh cells are dysregulated in CHB patients, potentially leading to impaired B-cell differentiation into plasma cells. Here, we found that although Tfh17 cell frequencies were decreased in CHB patients, they exhibited a more activated state. Activated Tfh17 cells correlated positively with HBsAg levels, while quiescent Tfh17 cells correlated negatively. Furthermore, CHB patients had higher frequencies of HBV-specific Tfh17 cells, which positively correlated with serum HBsAg and HBV DNA levels. Our study provides new insights into the role of Tfh17 cells in CHB infection, potentially informing immunotherapeutic strategies for functional cure.